2014
DOI: 10.1097/ta.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 17α-ethynylestradiol-3-sulfate for severe hemorrhage in minipigs in the absence of fluid resuscitation

Abstract: Administration of a single dose of 1-mg/kg EE-3-SO4 in 1-mL/kg of saline following severe hemorrhage increased survival in 60% acutely bled minipigs by 3.5-fold. Slightly elevated blood pressure values, more physiologic values of oxidative phosphorylation parameters, and lower elevations of possible tissue necrosis parameters correlated with longer survival time. These results support the further product development of EE-3-SO4 for the indication of severe hemorrhage when standard resuscitative fluids are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…21,26,27 Furthermore, sulfated ethinyl estrogens are highly soluble in the water, which is essential for effective drug distribution in tissues. 17,27,31 The rationale of DAI recovery by EE-3-SO 4 , however, is still not clear. We presume that EE-3-SO 4 alleviates traumatic axonal injury via increasing glucose uptake to stabilize ion channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,26,27 Furthermore, sulfated ethinyl estrogens are highly soluble in the water, which is essential for effective drug distribution in tissues. 17,27,31 The rationale of DAI recovery by EE-3-SO 4 , however, is still not clear. We presume that EE-3-SO 4 alleviates traumatic axonal injury via increasing glucose uptake to stabilize ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…42 EE-3-SO 4 can increase the cerebral circulation via its vasodilatory effects. 17,31,38 Neutralizing free radicals in the damaged area using antioxidants during the early stage of injury can result in significant reduction of inflammation, edema, and axonal breakdown. 51 Estrogens have strong antiinflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estrogen used here was 17β-estradiol, the most potent form of estrogen in females and has been widely employed in other researches [15]. The dose of 1 mg/kg BW of 17β-estradiol was chosen based on previous studies of estrogen in vivo, which was found to be optimal in producing salutary effects such as organ protection and maintenance of hemodynamics following adverse circulatory conditions [24,25].…”
Section: Treatment: 17β-estradiolmentioning
confidence: 99%
“…Trauma-hemorrhagic shock is known to be followed by many life-threatening sequelae [1], [2]. Trauma-hemorrhagic shock induces the overproduction of proinflammatory mediators, which plays an important role in the process of organ injury [3][5].…”
Section: Introductionmentioning
confidence: 99%